Influence of azolla, grass, water hyacinth, and peanut residues in amending soil properties - Uddin, M J; Rahman, A; Begum, K; Shafiq, F B; Tethy, S A (Journal of Biodiversity Conservation and Bioresource Management, 2023)
An incubation experiment was undertaken to evaluate the effects of azolla, grass, water hyacinth, and peanut residues for amending some soil properties. The experiment was laid out in pots comprising 7 treatments, viz. T1: Control, T2: Azolla (Azolla pinnata) @ 100 g/pot, T3: Grass (Phleum pretense) @ 100 g/pot, T4: Water hyacinth (Pontederia crassipes) @100 g/pot, T5: Peanut (Arachis hypogaea) @ 100 g/pot, T6: Azolla @ 50 g/pot + Water hyacinth @ 50 g/pot, and T7: Peanut@ 50 g/pot + Grass @ 50 g/pot. The results revealed that peanut treated soils (T5) played an important role in enhancing soil properties significantly (p < 0.05) and the values of soil organic carbon (SOC), pH, nitrogen, moisture content and cation exchange capacity (CEC) reached at an optimum level to support microbial growth over a year. Biodivers. Conserv. Bioresour. Manag. 2023, 9(2): 57-64